The effect of corporate governance factors on the quality of financial reporting in family and non-family firms - Borralho, J.; Gallardo-Vázquez, D.; Hernández-Linares, R.; Paiva, I. (Revista de Contabilidad - Spanish Accounting Review, 2020)
The objective of this study is to explore the quality of financial information of Spanish firms, by comparing family firms with non-family firms, and relating this quality with corporate governance practices. For this purpose, a sample of 650 Spanish firms was analysed during the period 2011-2016. Based on agency theory and socioemotional wealth literature, the results show a higher quality of financial information in family firms, a relationship which is reinforced by corporate governance factors. Our results are consistent with the scant previous research, and with the premises of agency theory, which indicate lower asymmetry of information between owners and managers in the singular context of family firms. Additionally, our work provides evidence that the participation of women on the board boosts the quality of financial information in family firms, contributing to the justification of family firm heterogeneity in terms of earnings management. This study contributes to reducing the gap in the literature on the influence of the family business context and the influence of women on the board on the quality of financial reporting.